Whatever Happened to Councillors? Problematising the Deficiency Narrative in English Local Politics. (August 2019) - Barnett, Neil John; Griggs, Steven; Howarth, David
Calls for councillors to change are nothing new, even from staunch defenders of local democracy. But one critical question has been sidestepped: Why have councillors been persistently constructed as a 'problem' for local government? This article draws upon Foucault to detect the emergence and sedimentation of an overriding problematisation of councillors. Our genealogical analysis of a range of public commissions and inquiries, policy documents and academic discourses reveals a 'deficiency narrative', forged during the managerialist turn in the 1960s and subsequently reframed in the 1990s and 2000s through the lens of community leadership. We show that the exclusions and methodological limits of this imaginary blinker studies of councillors, leaving an unhelpfully normative stance within local government studies. Such deficits also lead to a 'smoothing out' of the complexity of local politics, downplay local dynamics and political work, and miss important insights into the practices of local democracy.